2017
DOI: 10.1080/10934529.2017.1400793
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fuel components and combustion particle physicochemical properties on toxicological responses of lung cells

Abstract: The physicochemical properties of combustion particles that promote lung toxicity are not fully understood, hindered by the fact that combustion particles vary based on the fuel and combustion conditions. Real-world combustion-particle properties also continually change as new fuels are implemented, engines age, and engine technologies evolve. This work used laboratory-generated particles produced under controlled combustion conditions in an effort to understand the relationship between different particle prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 96 publications
1
17
0
Order By: Relevance
“…Statistical significant associations between OP and biological effects were reported in 22 of the 29 independent studies were statistical analysis were applied [29,32,43,44,49,52,57,58,59,60,63,65,66,74,75,76,77,78,79,80,81,82,83,84]: 10 independent studies reported that at least one OP measure was statistically significantly associated with all endpoints examined [43,49,52,57,63,66,78,79,80,81,83], while additional 12 independent studies reported that at least one OP measure was significantly associated with at least one effect outcome [29,32,44,58,59,60,65,74,75,76,77,82,84]. By contrast, seven studies reported no significant correlation/association between any OP measures and any biological effects [50,55,56,64,65,67,68,69,70,71,72,73] (Figure 1, and Tables S1 and S2, supplementary materials).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Statistical significant associations between OP and biological effects were reported in 22 of the 29 independent studies were statistical analysis were applied [29,32,43,44,49,52,57,58,59,60,63,65,66,74,75,76,77,78,79,80,81,82,83,84]: 10 independent studies reported that at least one OP measure was statistically significantly associated with all endpoints examined [43,49,52,57,63,66,78,79,80,81,83], while additional 12 independent studies reported that at least one OP measure was significantly associated with at least one effect outcome [29,32,44,58,59,60,65,74,75,76,77,82,84]. By contrast, seven studies reported no significant correlation/association between any OP measures and any biological effects [50,55,56,64,65,67,68,69,70,71,72,73] (Figure 1, and Tables S1 and S2, supplementary materials).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 22 studies that reported a statistically significant association between at least one OP measure and at least one or more biological effects, were 10 experimental in vitro or in vivo studies in cells or animals [29,32,43,44,49,50,52,55,56,57,58,59,60], and 11 epidemiological or clinical studies in humans [49,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84] (Figure 1). Of the seven independent studies reporting no statistical significant association between any OP measure and any biological effects were three independent experimental in vitro or in vivo studies [50,55,56], and four independent epidemiological or clinical studies [64,65,67,68,69,70,71,72,73] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations